(untitled) - Kelly, Gerald (Harlow, 2000)
Contents: The description of speech; teaching pronunciation; vowels; consonants; wors and sentence stress; intonation; pronunciation and spelling.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Pronunciation,Study and teaching,Foreign speakers,Học và dạy,Giáo trình dành cho người nước ngoài,Phát âm